Modifying Additives to Bitumen - Shukhrat Abdumalikovich Alikabulov (International Journal on Orange Technologies, 2021)
This article describes the testing of construction bitumen of the BN 90/10 brand with the addition of extract sludge, oil sludge and bleaching clay.